Final Chords of M.N. Pokrovsky’s “Brainchild”: Society of Marxist Historians in the Early 1930s - Victor Danilov (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2021)
Introduction. The Society of Marxist Historians established in 1925 went down in the history of Soviet historiography as a militant organization that did much to combat “old school” historians, assert the monopoly position of the Marxist-Leninist methodology, and draw a party line in historical science. Methods and materials. The research is based on traditional methods of historiographical analysis. It uses materials from historical journals of the 1920s and 1930s and archival documents. Analysis. The first all-Union conference of Marxist Historians (December 28, 1928 – January 4, 1929) became the apogee in the history of the Society. In the future, despite the growth in numbers and the creation of local structures, in the conditions of the “great turning point” it loses the features of an amateur organization and a number of functions of the scientific nature. The priority is to “actively participate in the socialist construction” by deploying mass propaganda of historical knowledge and fighting “distortions of Marxism-Leninism”, including in the ranks of the organization itself. The last debate and “study” of Stalin’s famous letter to “Proletarian revolution” journal had a negative impact on the internal state of the Society and strengthened the distrust of the results of his work from the government. In 1931–1932, the Society management unsuccessfully tried to make its work more popular, hold a plenum and re-registered a new charter. Results. However, at that time, the Central Committee of the CPSU(b) embarked on the path of reformatting the structure of societies and unions in the country and eliminating those of them that had exhausted their mobilization potential and did not meet the new ideological course. In addition to this circumstance, the rapid curtailment of the Society of Marxist historians by the end of 1932 was influenced by the position of the leadership of the Communist Academy and the death of M.N. Pokrovsky, the undisputed leader of Soviet historians.